Small cell carcinoma lung presented as both Pancoast and superior vena cava syndrome: a case report - Rajdeep Basu; Sukalpa Chaudhuri; Soumitra Ghosh (SpringerOpen, 2018)
Superior vena cava (SVC) syndrome occurs because of SVC obstruction by mediastinal mass, with features of venous stasis and Pancoast syndrome manifested by tumour of the lung apex with features of invasion to adjacent bones, soft tissues and the nervous system. Small cell carcinoma lung is commonly found to cause SVC syndrome, Pancoast is a rare association. Only a few cases have been reported so far. In this report, we focus on a 45-year-old male patient who presented with both Pancoast and SVC syndrome because of small cell carcinoma of the lung.